Correlation analysis between peripheral blood basophils and disease activity in patients with rheumatoid arthritis - Na Zhang; Ze-Ming Zhang; Xiao-Fei Wang (SAGE Publishing, 2018)
This study set out to investigate the number and the activation of peripheral blood basophils, and the correlation analysis between peripheral blood basophils and disease activity in patients with rheumatoid arthritis (RA). It was determined whether these indices could be used as a monitoring index of RA activation and thereby provide a new disease assessment method for RA. Using flow cytometry, the number and activation level of peripheral blood basophils were determined in RA patients compared with healthy donors. General clinical data were collected and laboratory indices of RA patients were analyzed. A correlation between the number and the activation of basophils was determined using the Disease Activity Score 28 (DAS28), anti-cyclic citrullinated peptide (CCP), erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP).The absolute count and percentage of peripheral blood basophils in RA patients were significantly lower than that of controls (absolute count P  = 0.033, percentage P  = 0.047). However, the activation level of basophils was significantly higher than that in controls ( P  = 0.034). In addition, the activation level of basophils showed statistically significant differences in disease groups with different activities ( P  = 0.011, P  = 0.037, and P  = 0.002). With an increasing DAS28 score, the number of peripheral blood basophils was shown to decrease while activation level increased. The absolute count and activation level of basophils in RA patients and normal controls on receiver operator characteristic (ROC) curves were (area under the curve (AUC) = 0.676, P  = 0.025; AUC = 0.694, P  = 0.014), respectively, which were statistically significant in differentiating RA patients from controls. The activation level of basophils was positively correlated with CCP ( P  < 0.001, r = 0.831), was positively correlated with CRP ( P  = 0.001, r = 0.588). These data are correlated with disease activity assessment and can be used as an early monitoring index of RA activity. Therefore, these studies provide a new basis for evaluation of clinical disease activity in RA patients.